2021
DOI: 10.1177/01939459211050955
|View full text |Cite
|
Sign up to set email alerts
|

Theoretically Based Factors Affecting Stroke Family Caregiver Health: An Integrative Review

Abstract: Stroke family caregivers often neglect their own health while providing care. Rigorous reviews have focused on stroke caregiver needs and outcomes; however, a comprehensive review of stroke caregiver health is lacking. The purpose of this integrative review was to determine factors associated with stroke family caregiver health. Using a PRISMA flow diagram and Rayyan software, 41 studies were identified published from January 2000 to December 2020. Databases included Cochrane Reviews, Cochrane Trials, PsycINFO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 83 publications
(253 reference statements)
2
5
0
Order By: Relevance
“…Among all of the theoretically based factors, depressive symptoms were found to be the most important factor associated with unhealthy days. These results are in line with other reviews of stroke family caregiver health, which have found depressive symptoms and caregiver burden to be significant factors that affect stroke family caregiver health (Kum et al, 2022). These findings underscore the urgent need to screen and treat family caregivers of persons who have had strokes for depressive symptoms to preserve their health while providing care.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among all of the theoretically based factors, depressive symptoms were found to be the most important factor associated with unhealthy days. These results are in line with other reviews of stroke family caregiver health, which have found depressive symptoms and caregiver burden to be significant factors that affect stroke family caregiver health (Kum et al, 2022). These findings underscore the urgent need to screen and treat family caregivers of persons who have had strokes for depressive symptoms to preserve their health while providing care.…”
Section: Discussionsupporting
confidence: 92%
“…Although many studies have focused on depressive symptoms (Bakas et al, 2015;Byun et al, 2019), few have studied the factors affecting stroke family caregiver health. Stroke family caregivers tend to neglect their own health as they provide care to their loved ones (Bakas et al, 2014(Bakas et al, , 2022Kum et al, 2022). As a result, it is important to study the factors affecting stroke family caregivers' health, thus providing them with better tools to manage their own health.…”
mentioning
confidence: 99%
“…However, in low- and middle-income countries, caregivers play rehabilitation roles, creating an immense emotional and physical strain on them. [ 6 ] Furthermore, caring for a stroke patient is burdensome, and may influence several objective and subjective aspects of the caregiver's life, such as physical and emotional health, morale, work-life balance, finances, social mobility, interpersonal relationships, and sex life. Consequently, studies have reported alarmingly higher levels of anxiety and depression among caregivers of stroke patients, varying from 17–50%.…”
Section: B Ackgroundmentioning
confidence: 99%
“…Often, the responsibility of care falls on a single family member, encompassing physical, mental, and emotional challenges that complicate management at home and work (7)(8)(9)(10). This dynamic can lead caregivers to neglect their own health needs (11,12). People with SCI rely on their families for nutrition and routine care, which significantly improves their quality of life and ability to engage in society (13).…”
Section: Introductionmentioning
confidence: 99%